Effect of Consumer Ethnocentrism on Perceived Quality and Repurchase Intention of Indonesia Movie (Pontianak Case Study) - B12112008, Saldi Primadiputra (Jurnal Manajemen Update, 2017)
Indonesian movie it’s in very unique condition, Indonesian Ethnocentrism Tendencies is quite high but because the quality is having condition that some of genre showing high quality, but some others have lower quality, so there isn’t stagnant condition that affect the customer demand to repurchase intention in cinema. This research aims at analyzing the effect of ethnocentrism toward perceived quality and repurchase intention of Indonesian movie that exclusively happening in Pontianak city. The sample is selected by using random sampling method. The result of this research shows that Consumer Ethnocentrism Tendencies have positive and significant effect towards Repurchase Intention, but perceived quality have positive but not significant effect toward repurchase intention when become an intervening variable between consumer ethnocentrism tendencies variable.